PHARMACEUTICAL AND ANALYTICAL STUDY OF PINDA TAILA (International Journal of Ayurveda and Pharma Research, 2021)
Rasashastra and Bhaishajya Kalpana is the branch in Ayurveda which deals with herbal and herbo-mineral drugs. The specialized branch which deals with identification, collection, processing, compounding and dispensing of Ayurvedic drugs is called as Bhaishajya Kalpana. Ayurvedic Dosage forms are exclusive in their pharmaceutics and therapeutics. Sneha Kalpana can be defined as pharmaceutics of medicated Taila and Ghee. These drugs treat a very wide range of diseases among patients of all age groups. In the context of Sneha Kalpana, Taila and Ghrita are supposed to undergo the process called Murchchhana Samskar through which better therapeutic value can be incorporated into the raw material which enhances its absorption into the biological systems. The Taila acts not only as a base or vehicle but also as a class 1 preservative. Pinda Taila was prepared using the ingredients Manjishtha, Sariva, Rala, Madhuchchhishta and Tila Taila. An attempt was made to validate the pharmaceutical preparation of Pinda Taila. It was prepared according to the norms of Ayurvedic classical texts. In the present study, detailed pharmaceutical processes and physicochemical evaluation of Pinda Taila were carried out. The physicochemical parameters included Specific gravity which was found to be 0.9627, Refractive index 1.488, Iodine value 5.88, Acid value 0.15, Saponification value 233.31, and Peroxide value 7.55. HPTLC evaluation showed variable numbers of spots when visualized in all three wavelengths. However, the chemical constituent could not be identified in the absence of a standard marker compound.